1995
DOI: 10.1007/bf01719311
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior of women with repeated episodes of vulvovaginal candidiasis

Abstract: One hundred and two women with a history of a median of six episodes of vulvovaginal candidiasis (VVC) and 204 age-matched controls participated in a structured in-depth interview on sexual behavior. Mean and median ages of the two groups were 26.7 and 26 years, respectively. Sexual characteristics, associated with VVC in crude analyses, were adjusted in multifactorial analyses for coital frequency, experience of casual sex, vaginal irritation, smoking, alcohol habits, and having a steady partner. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
2
21
2
Order By: Relevance
“…This was not in agreement with the findings of Hellberg et al and Rathod et al that reported age of sexual debut; casual sex partners and regular oral sex being associated with repeated VVC. (33,34) However, this is in agreement with the findings of Corsello et al that believed that increased number of sexual partners, age of sexual debut and increased frequency of sexual intercourse were not significantly risk factors associated with VVC. (35) Douching has been documented to be an important risk factor for the acquisition of vulvovaginal candidosis in previous studies (34,36) .In our study, seven (25.9%) of the women who had VVC usually practice douching , however, this was not found to be statistically significant (p=0.171).…”
Section: Discussionsupporting
confidence: 91%
“…This was not in agreement with the findings of Hellberg et al and Rathod et al that reported age of sexual debut; casual sex partners and regular oral sex being associated with repeated VVC. (33,34) However, this is in agreement with the findings of Corsello et al that believed that increased number of sexual partners, age of sexual debut and increased frequency of sexual intercourse were not significantly risk factors associated with VVC. (35) Douching has been documented to be an important risk factor for the acquisition of vulvovaginal candidosis in previous studies (34,36) .In our study, seven (25.9%) of the women who had VVC usually practice douching , however, this was not found to be statistically significant (p=0.171).…”
Section: Discussionsupporting
confidence: 91%
“…However, an association between RVVC on the one hand, and frequent intercourse on the other, has been shown 28 . First intercourse at young age, sex during menstruation and casual sex during the previous month have also been associated with RVVC 29 .…”
Section: Relapse or Reinfection?mentioning
confidence: 99%
“…The theory that recurrence may be due to reinfection of the woman by her male sexual partner has been suggested repeatedly with some data indicating that sexual transmission does occur [65,66,69]. Candida spp may be harboured in the male GIT, semen, oral cavity and urine [78,138], and male colonization is often associated with vaginal colonization often with the same strain of Candida [66,139].…”
Section: Discussionmentioning
confidence: 99%
“…Candida spp may be harboured in the male GIT, semen, oral cavity and urine [78,138], and male colonization is often associated with vaginal colonization often with the same strain of Candida [66,139]. Studies have indicated that oral sex performed by the male partner (cunnilingus) is associated with both incident and recurrent candidiasis [65,69]. Bailey et al [67] reported an increased risk of genital candidiasis among women who have sex with women (WSW), which rose with number of partners [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation